Наш опыт закрытого интрамедуллярного остеосинтеза проксимальных переломов плечевой кости - Ивченко, Д. В.; Яцун, Е. В.; Москальков, А. П.; Миренков, К. В.; Кирпиченко, С. Ф.; Трашков, В. Д; Ivchenko, D. V; Yatsun, E. V.; Moscalcov, A.P.; Mirenkov, К. V; Kyrpychenko, S. F.; Trashkov, V. D.; et al. (К. : Юстон, 2017)
Цель работы: апробация методики закрытого БИОС при проксимальных, двух - и трех - фрагментарных, 2-3 тип по (Neer) переломах плечевой кости, в условия отделения травматологии с койками политравмы КУ ГКБЕ и СМП г. Запорожья. Aim of the study: approbation of the method of closed IM nailing in proximal two- and three-part humeral fractures, 2-3 type by Neer upon conditions of traumatology department with polytrauma beds at Cl "Municipal Clinical Hospital of Emergency and First Aid".
Our experience of intramedullary nailing of proximal humerus fractures
Keywords: перелом; плечевая кость; закрытая репозиция; интрамедуллярный остеосинтез; fractures; humerus; closed reposition; intramedullary nailing.